Development of a Model for Plaque Induction in Rat Carotid Arteries - Wakako, Akira; Sadato, Akiyo; Oeda, Motoki; Higashiguchi, Saeko; Hayakawa, Motoharu; Oshima, Marie; Hirose, Yuichi (Asian Journal of Neurosurgery, 2023)
Objective Plaque induction through intimal injury using a balloon catheter in small animals and by artificial ligation of the carotid artery in large animals have been reported. However, these reports have not yet succeeded in inducing stable plaques nor creating a high degree of intimal thickening to be used as animal models. We have previously developed a plaque induction model in rats but have failed to obtain a plaque incidence frequency that can be used as a model. Thus, in the current study, we aimed to create a versatile disease model to examine the pharmacokinetics of drug administration, determine the efficacy of treatment, and examine the process of intimal thickening. We also attempted to create an improved model with shorter, more frequent, and more severe intimal thickening.Materials and Methods The common carotid artery of male Wistar rats was surgically exposed and completely ligated with a wire and 6–0 nylon thread. Then, the wire was removed to create a partial ligation. To create a high frequency and high degree of intimal thickening, 72 rats were divided into two groups: a single lesion group with a 0.25-mm wire and a single ligature point, and a tandem lesion group with a 0.3-mm wire and two ligature points. Each group was further divided into normal diet and high cholesterol diet groups. The presence and frequency of intimal thickening were examined for each group after 4, 8, and 16 weeks of growth.Results In the single lesion group, intimal thickening was observed in 42% of the 4-week group and 75% of the 8-week group. In the tandem lesion group, intimal thickening was observed in 75% of the 4-week group and 50% of the 8-week group. In addition, 50% of the individuals reared for 16 weeks developed intimal thickening.Conclusion We successfully induced intimal thickening in the carotid arteries of rats with high frequency in the single lesion and tandem lesion groups. The results also showed that the tandem lesion group tended to induce intimal thickening earlier than the single lesion group.
Keywords: animal model; arteriosclerotic plaque; carotid artery; computational fluid dynamic; intimal thickening; rat